Post Traumatic Spinal Cord Transsection – A Case Series (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Road traffic accidents are increasing as an alarming annual rate of three percent in India experiencing an increasing trend in spinal injuries. Spinal cord transsection is becoming prevalent day by day and has become an important aspect in medicolegal autopsy [1]. The present study aims to assess the anatomical distribution of spinal injuries corresponding to its relation with mechanical trauma and also focuses on various causative factors of spinal injuries. Study also emphasis to assess spinal cord in different cases of mechanical trauma. Spinal cord transsection is a complete interruption of white matter tracts, segmental grey matter, and associated nerve roots in spinal cord at any point between cervical- medullary junction and tip of conus medullaris. Depending upon the level of transaction, it may prove to be fatal or lead to permanent disability below the level of transection. It has been found to affect mostly young active individuals. The most common cause of spinal cord transection is penetrating injuries such as knife wounds or severe trauma such as vertebral fracture–dislocations or a complicated childbirth [2]. We present 4 cases of complete spinal cord transsection, observed at post-mortem examination of road traffic accident victims and fall from height.
Keywords: Spinal cord transsection; Road traffic accident; Fall from height